Japanese Bunker Banyuwangi Left As A Laboratory For Learning History - Miskawi, Miskawi; Shomad, Abdul (History Education, University of Jember, 2022)
There are many Japanese bunkers in Banyuwangi Regency, one of which is in Blimbingsari District. Bunkers have not been recorded and used as a source for historical knowledge. Considering that the goal of this study is (1) list the Japanese bunkers in Bimbingsari, Banyuwangi Regency, and (2) explain how they are used as a history learning lab. The descriptive-analytical research methodology was employed.. Information supplied through surveys, interviews, and literature reviews. A spatial method of data analysis was used. A scientific method is used when using bunkers in the educational process. According to the findings of the research, six bunkers with the designations BLB-BM 01, BLB-BM 02, BLB-BM 03, and BLB-BM 04 that are situated in Pantai Ria, Bomo Village, Blimbingsari, and Banyuwangi. Keywords: Bunker, Japan, Laboratory, Education, History